Using the Congklak Game to Improve Mathematics Learning Outcomes in Elementary School Students - Sumarni, Titin; Andriyansyah, Andriyansyah; Elmefi, Sacia; Nurhasanah, Nurhasanah; Taufik, Anton (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Learning math requires media that can attract students' attention and interest them in the subject. Generally, students love games, making them an effective tool to engage students in the learning process. The use of appropriate media can increase students' success in learning mathematics. This study aims to explore and describe the improvement of students' mathematics learning outcomes through the use of Congklak Game Media. This study used the Classroom Action Research method and was conducted in an elementary school in Indonesia. The research informants consisted of teachers and twenty-four students. Data were collected through observation, documentation, and test techniques, and analyzed qualitatively using descriptive analysis. The findings of this study showed an increase in students' mathematics learning outcomes. This increase can be seen from the cumulative score, where the pre-test score increased from 67% to 92% in the second cycle. This shows that the congklak game media can be an effective tool to improve students' math learning outcomes.